Iterative algorithms for finding a common solution of system of the set of variational inclusion problems and the set of fixed point problems - Atid Kangtunyakarn (My University, 2011)
Abstract In this article, we introduce a new mapping generated by infinite family of nonexpansive mapping and infinite real numbers. By means of the new mapping, we prove a strong convergence theorem for finding a common element of the set of fixed point problems of infinite family of nonexpansive mappings and the set of a finite family of variational inclusion problems in Hilbert space. In the last section, we apply our main result to prove a strong convergence theorem for finding a common element of the set of fixed point problems of infinite family of strictly pseudo-contractive mappings and the set of finite family of variational inclusion problems.
Keywords: Finite set; Family of sets; Optimization and Variational Analysis